The integration of caklempong music into mobile game in instilling Malaysian youths' interest on traditional music / Fatimah Zahra Ros Azman - Azman, Fatimah Zahra Ros (2016)
Malay traditional music is a Malaysian heritage that needs to be preserved in order to maintain the identity of Malaysia. However, these kinds of music especially caklempong traditional music is still unfamiliar among younger generation. Traditional music has facing an issue since generation nowadays are preferred on popular music rather than these kinds of music. Therefore, the aimed of this research was to preserve the caklempong traditional music by translating it into a musical mobile game in instilling Malaysian youths' interest on traditional music. This research was conducted to measure the youths' awareness towards this music, to identify the most appropriate game design contents in designing a caklempong music mobile game and to measure the effectiveness of caklempong mobile game application in encouraging Malaysian youths' interests towards this music. In order to conduct the research, a Waterfall model has been adapted as research framework of the whole research flow. The phases have involved both qualitative and quantitative method which comprised of pilot study, design prototype, pre and post-test. In pilot study, the survey questionnaires have been distributed randomly to 81 respondents via online surveys in order to achieve the first and second research objectives. Besides, the interview sessions were conducted with 5 interviewees to collect data regarded to the main issue. The result collected from this pilot study were respondents' level of awareness on traditional music and their preferences on game design contents. Based on the result of pilot survey, the prototype was designed based on respondents' preferences in order to be tested in the pre-test. Pre and post-test were conducted using cluster sampling at three higher education institutions in Shah Alam; UiTM, Unisel and MSU by testing the prototype and distributing questionnaires at random sample of 20-25 years old students. The result of pre-test has been used to redesign the prototype to be tested in post-test. The data collected from the post-test has showed that mobile game is an effective medium to entice youths' interest towards traditional music.